Pemodelan Anomali Self Potential (SP) Menggunakan Algoritma MVDE (Multi Variant Differential Evolution) - Muhammad Budi Haryono; Yekti Widyaningrum; Herman Aldila (Jurnal Riset Fisika Indonesia, 2023)
Self Potential (SP) is a practical and simple geophysical method. Interpretation of the data of these methods can be done qualitatively and quantitatively. Quantitative interpretation can be done through inversion modeling, but inversion modeling often has problems with the solution of model parameters that are stuck at local minima. Therefore, in this study the MVDE (Multi Variant Differential Evolution) algorithm is used which is able to solve model parameter problems, by finding global model parameter solutions. Inversion modeling of observation Self Potential (SP) anomaly data is carried out using an algorithm that has been tested and produces a misfit of ≤10%, the test aims so that the algorithm can be used further to model observation data. The observation Self Potential (SP) anomaly modeling produces model parameter values ​​K=609.3mV D=9.3 h=3.75m q=1.51 and x=1-16, with a subsurface anomaly model in the form of a spherical geometry at depth 3.75m.